Kegiatan Pelestarian Sungai Afvoer Kemambang untuk Meningkatkan Rasa Tanggung Jawab Masyarakat terhadap Lingkungan di Waru Sidoarjo - Wibowo, Agung Satrio; Khoiro, Imaniha; Darmawan, Didit; Saputra, Rio; Waskito, Sarwo (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
The Afvoer Kemambang River Cleanup program aims to analyze the implementation of river conservation programs as a strategy to increase community responsibility for environmental sustainability in Waru District, Sidoarjo. The river previously experienced blockages due to garbage accumulation and the growth of water hyacinth, indicating low public awareness of environmental cleanliness. This activity involved residents in concrete actions that improved the river ecosystem while providing a positive example for the wider community. The Participatory Action Research (PAR) approach was applied to involve the community from planning, coordination, and implementation of the activity. The activity began with a general briefing and division of tasks, followed by cleaning the river flow and removing garbage from the riverbanks. The results showed increased environmental awareness, social solidarity, and a sense of responsibility from residents towards nature conservation. It is recommended to expand this program to other areas with greater participant involvement and government support to ensure sustainable river conservation. Community participation has been proven to improve river conditions and foster a culture of sustainable environmental care, making this program a replicable model for community empowerment in other regions.